REPRESENTATION OF THE CONCEPT OF BEAUTY IN THE FORMATION OF SACRED SPACE OF THE 20TH CENTURY - Gnatiuk, Liliia (Theory and practice of design, 2024)
The development of the concept of beauty from the times of pagan Ancient Rome and Greece to Christian Rome and Athens and to the present is analyzed. From elevation to functionality. The opinions of leading theorists of culture are presented. Features characteristic of the culture of the 20th century are represented. The architecture of sacred buildings built according to the principle of traditional forms, as well as the symbolic meaning of the work of art, are considered. It was determined that the objects created at that time, despite their modern appearance, their interpretation as an area of rational satisfaction of purely material and technical needs, solving utilitarian tasks, bear the semantic features of traditional temples. It was found that the defense of the position of beauty and art at that time focused on arguments that were easy to refute. Cooperation with artists became a sign of rejection of the modernist thesis that architectural activity is constructive or research- scientific rather than artistic. A tendency towards historical and traditional reminiscences has been revealed. Goal. To reveal the peculiarities of the representation of the concept of beauty in the formation of the sacred space of the 20th century. Methodology. Theoretical research methods, analysis of foreign experience in building temples were used. The grapho-analytical method is applied. The results. Identification of the features of the representation of the concept of beauty in the formation of the sacred space of the 20th century. Scientific novelty. The view that beauty and adornment in certain theories of that time did not have transcendental causes is presented. Although individual elements of decoration were intended to tame sensuality. Practical significance. The forms of individual sacred buildings and methods of organizing their interiors in modern forms, which can be used in the further development of temple architecture, are analyzed. The use of the metaphorical language of architecture based on the world of visual human products and their iconographic distinctive features is considered. The need to take into account the relationship between certain forms and the messages transmitted through them in shaping the sacred space has been revealed.